The Impossible Stability? The Italian Lower House Parliamentary Elite After a “Decade of Crises” - Verzichelli, Luca; Marino, Bruno; Marangoni, Francesco; Russo, Federico (Frontiers in Political Science, 2022)
The article explores recent changes in the Italian parliamentary elite thanks to a novel set of data on Italian MPs between 1946 and 2018. After a first discussion on some crucial long-term trends of Italian Lower House MPs (their turnover rate, seniority, gender balance, party-related or institutional experience), we focus on the possible explanations of the profound transformation that occurred in the past decade: the rise of new party actors, the realignment between citizens and the parliamentary elites, or the use of different electoral systems. Subsequently, we point at three MP categories, taken as the most relevant proxies of the innovations in the Italian parliamentary elite. These categories are based on the length of MPs' parliamentary career, their previous party or institutional experience, and their gender. We discuss the changing numerical relevance of these categories, their parliamentary career patterns, and some features related to the institutionalization of MPs belonging to such categories. Two implications clearly emerge from our analysis. First, the changes occurred in the so-called “decade of the crises” (after the 2013 and 2018 Italian general elections) are critical in terms of a new influx of political amateur, female, and young MPs. The magnitude of this renewal can hardly be compared to any other relevant turning point of the Italian republican age and might signal the existence of a pattern of “impossible stability” for the parliamentary elite. Second, and partly in contrast with the first implication, despite such changes, the perspectives of parliamentary career and parliamentary survival remain very much subordinated to belonging to strong parliamentary party groups. This signals that, despite broad discussions about the positive role exerted by new political actors and the demand for a stronger descriptive representation, what seems to matter in the Italian Lower House is the presence of powerful political parties.